Short term effect of virtual reality headset on blink rate and inter-blink interval - Zaini, Nurul Hafizah; Che Azemin, Mohd Zulfaezal; Ithnin, Mohd. Hafidz; Mohd Tamrin, Mohd Izzuddin (RMP Publication, 2020)
Virtual reality (VR) headsets are becoming remarkably well-known nowadays, especially in gaming industry. Their ability to immerse users into virtual world makes them captivating. However, there is limited research about the impacts of this technology on our eyes and vision. This study investigated if there is any effect on blink rate (BR) and inter-blink interval (IBI) after 30 minutes of watching 3-dimensional (3D) movie on VR. Besides, this study compares between watching 3D movie on VR headset and 2D movie on laptop. Blinks were recorded over 1 minutes for 32 participants volunteered in this study before and after 30 minutes of watching 3D movie on VR headset and 2D movie on laptop. The result of BR and IBI between pre- and post-watching 3D movie on VR was not significant (p= >0.05). The result between watching movie on laptop and VR also not significant (p= >0.05). Watching 3D movie on VR for 30 minutes resulted in no effects on blink rate and inter-blink interval of the users.